Some Ceramic Contributions to a Knowledge of Culture in Prehistoric Iran - Vanden Berghe, Louis (1966)
published by the Wenner-Gren Foundation for Anthropological Research, Inc.; = Viking Fund Publications in Anthropology, edited by Sol Tax, vol. 41; Geoy Tepe, Hasanlū, Chashmah-i ‛Ali Tepe, Tepe Siyalk, Tepe Ḥiṣār, Anau, Tūrang Tepe, Shāh Tepe, Tepe Giyān, Khūzistān: Susa; Fars: Tall-i В akūn; Bampūr, Khurāb.